Preliminary checklist of orchids in the Sungai Kangkawat, Imbak Canyon Conservation Area (ICCA), Sabah, Malaysia - Edward Entalai Besi; Dome Nikong; Vanilie Terrence Justine; Farah Alia Nordin; Ahmad Asnawi Mus; Heira Vanessa Nelson; Nurul Najwa Mohamad; Nor Azizun Rusdi; Rusea Go (Universiti Malaysia Sabah, 2020)
A study on orchids diversity was carried out in the Sungai Kangkawat, Imbak Canyon Conservation Area (ICCA), Sabah, Malaysia. The study aimed to record species composition and distribution of orchids in the furtherance of orchid conservation objective in the gazetted conservation area. A total of 95 species and 30 genera were collected from South Rim, Kawang, and Nepenthes trails. The collection consists of 91 epiphytes, two terrestrials, and two mycoheterotrophs. More orchids were found in the riverine than inland areas. Our study on the species composition based on the vegetation types shows that the presence of inconspicuous and achlorophyllous, either mycoheterotrophic or leafless epiphytic orchids, are indicators of the undisturbed vegetation types. Though the finding was preliminary and brief, our encounter of endemic and rare species underlines the importance of Sungai Kangkawat forest area as an orchid biodiversity hotspot.